Bibliometric Analysis of Public Service Digitalization in Villages: Mapping Trends and Collaboration Networks - Irman Puansah (Khazanah Sosial, 2025)
Digital transformation in governance has become a global priority, yet research on the digitalization of public services in rural villages remains fragmented and underexplored. Limited infrastructure, disparities in digital literacy, and institutional readiness highlight the urgency of mapping existing scholarship to identify research trends and gaps. This study aims to provide a systematic overview of the literature on village-level public service digitalization through bibliometric analysis of Scopus data published between 2015 and 2025. Methods include trend analysis of publications, distribution of documents, co-authorship networks among authors and institutions, and keyword co-occurrence analysis using VOSviewer. Findings indicate that publications on this topic are still limited but show a rising trend in recent years, dominated by multidisciplinary journals in the social sciences. Contributions come primarily from developing countries, especially India and Indonesia, with research themes focusing on digital skills development for village officials, community participation, and policy support. Collaboration networks among authors and institutions remain weak, reflecting a fragmented research community. This study contributes by clarifying the current state of knowledge, highlighting the relevance of e-Government, Sociotechnical Systems, Digital Divide, and Citizen-Centric Government theories, and recommending stronger international collaboration to accelerate inclusive and effective implementation of digital public services in villages.